Experimental and analytical study on the mechanical behaviour of cable bolts subjected to axial loading and constant normal stiffness. (January 2019) - Li, Danqi; Masoumi, Hossein; Hagan, Paul C.; Saydam, Serkan
Abstract: This study aims to experimentally and analytically investigate the behaviour of two different cable bolts, including Sumo and TG using an advanced pull-out testing facility capable of testing the cable bolts under axial loading and constant normal stiffness. The quantitative contribution of a range of parameters (e.g. uniaxial compressive strengths of grout and confining medium and the borehole diameter) on the overall behaviour of Sumo and TG cable bolts was examined based on Analysis of Variance (ANOVA). It was found that the confining medium strength was the most effective factor to the peak load and the initial stiffness of Sumo cable bolt. For the TG cable bolt, the grout strength was determined as the most significant parameter. Overall, a rise in the strength of grout and/or confining medium resulted in an increase in the peak load of both Sumo and TG cable bolts. In addition, a new analytical model was developed to simulate the load-displacement behaviour of modified cable bolts. The model can predict the linear elastic behaviour of cable bolt as well as the non-linear response. The non-linear behaviour was captured through an algorithm in which, an increase in the axial displacement led to an incremental increase in the axial load where the cable bolt was subjected to a constant normal stiffness. The model was then validated using the experimental data resulted from the pull-out tests on the Sumo cable bolt. An acceptable agreement between the experimental data and the model simulations confirmed the capability of the developed analytical model for the behaviour prediction of modified cable bolts under constant normal stiffness.